2020
DOI: 10.1017/s1431927620024599
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructure of Antennal Morphology and Sensilla of Teak Skeletonizer, Eutectona machaeralis Walker (Lepidoptera: Crambidae)

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…Likewise, similar attention has been given to antennal sensillar structures in lepidopteran forest pest species. They include the teak skeletonizer Eutectona machaeralis (Lan et al 2020), the spruce budworm Choristoneura fumiferana (Albert and Seabrook 1973) and the Chinese pine caterpillar Dendrolimus tabulaeformis (Zhang et al 2013). A comparative analysis of the antennae of Trichoptera, and basal and derived Lepidoptera species, revealed that a relationship exists between the proportions of certain sensilla types, and the type of sex pheromone used (Yuvaraj et al 2018).…”
Section: Sensory Perceptionmentioning
confidence: 99%
“…Likewise, similar attention has been given to antennal sensillar structures in lepidopteran forest pest species. They include the teak skeletonizer Eutectona machaeralis (Lan et al 2020), the spruce budworm Choristoneura fumiferana (Albert and Seabrook 1973) and the Chinese pine caterpillar Dendrolimus tabulaeformis (Zhang et al 2013). A comparative analysis of the antennae of Trichoptera, and basal and derived Lepidoptera species, revealed that a relationship exists between the proportions of certain sensilla types, and the type of sex pheromone used (Yuvaraj et al 2018).…”
Section: Sensory Perceptionmentioning
confidence: 99%
“…Afterward, specimens were critical-point dried for 1 h with CPD 030 (Micro Technology Hong Kong Ltd., Hong Kong, China), and then mounted on a holder from two sides, the dorsal side and ventral side, using double-sided adhesive tape and gold coated with the Eiko IB•3 Ion sputter coater (Hitachi, Tokyo, Japan). Sensilla were observed and micrographs were captured from different directions at 10 kV using the QUANTA 200 FEG scanning electron microscope (Feicompany, Hillsboro, OR., USA) (Lan et al, 2020).…”
Section: Scanning Electron Microscope (Sem)mentioning
confidence: 99%
“…Eutectona machaeralis (Walker) (Lepidoptera: Crambidae), is a serious pest that feeds on the mesophyll of teak, leading to a significant decline in the photosynthesis of the leaves. 4 The annual outbreak of these pests happens in teak-growing regions of China, India, and Malaysia. 5 The P. machaeralis females deposit their eggs near the midrib of the leaves, completing the life cycle within 23 days.…”
Section: ■ Introductionmentioning
confidence: 99%
“…However, the leaf skeletonizer, Pyrausta machaeralis (Walker) syn. Eutectona machaeralis (Walker) (Lepidoptera: Crambidae), is a serious pest that feeds on the mesophyll of teak, leading to a significant decline in the photosynthesis of the leaves . The annual outbreak of these pests happens in teak-growing regions of China, India, and Malaysia .…”
Section: Introductionmentioning
confidence: 99%